Some considerations on the Industrial Remuneration Conference, 1885 - Bastable, C. F. (Statistical and Social Inquiry Society of Ireland, 1885)
There has been an increasing tendency of late years to give greater prominence to social as opposed to political questions, and to bring more distinctly into notice the various plans suggested for social reform. One evidence of this changed feeling is to be found in the meeting of the Industrial Remuneration Conference. The aim of the originator of that conference was to bring before the public the opinions of the most widely separated schools of thought, as to what is known on the continent as the ?Social Question?.
Read before the Society, 30 June 1885
Keywords: Industrial Remuneration Conference, 1885; Income inequality; Equity in Ireland; 314.15